Terapia Manual Ortopédica para el alivio del dolor lumbar del adulto - Jiménez Jiménez, Jordan Adrian (2022)
ABSTRACT: The research carried out was of a bibliographic type where a series of scientific articles were compiled, of which 35 were included in the research work. Thus, after the search in scientific databases such as Pubmed, Scielo, Google Scholar, Cochrane, PEDro, Elsevier, Dialnet, ScienceDirect, it has been demonstrated that low back pain is a pathology that affects a high percentage of the population not only at a national or continental level, but also worldwide, This occurs because the area that suffers the greatest impact and overload is the lumbar area, which is affected by the activities during work or daily life of people; however, it is not the only aspect to take into account, since it influences other areas such as the physical, social and mental. Taking into account the adverse effects of the pathology, it has been proposed to give a solution to it, that is why Orthopedic Manual Therapy consists of an effective treatment to alleviate the symptoms that afflict achieving pain relief, joint limitation, decrease in the quality of life, in addition to reducing the degree of disability in individuals who suffer from low back pain, because of this the psychological area is affected since people begin to trigger both anxiety and depression. The treatment is not exclusive, but is integrated with other techniques such as myofascial release, dry needling and spinal manipulation each with specific effects, however, it is important to emphasize that individually its benefits are minimal for this reason it should be complemented with a personalized exercise plan to create a treatment that provides welfare and confidence in the patient, in order to achieve that the effects persist in the patient.